2024
DOI: 10.1002/ejhf.3189
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐diagnostic free androgen and estradiol levels influence heart failure risk in both women and men: A prospective cohort study in the UK Biobank

Jungeun Lim,
Maryam Hashemian,
Batel Blechter
et al.

Abstract: AimsSerum sex hormones have been linked to cardiovascular disease risk. However, their roles in the pathogenesis of heart failure (HF) in both men and women are unclear. We investigated the associations between free androgen, testosterone, and estradiol, and future risk of HF.Methods and resultsThis prospective cohort study evaluated UK Biobank participants free of prevalent cardiovascular disease and HF at baseline. Unitless free androgen, testosterone, and estradiol indices were generated using serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…CRP is a pro-inflammatory cytokine that can trigger the release or is correlated with other inflammatory markers such as interleukin-6, interleukin-8 and tumor necrosis factor-α ( 27 ), which suggests possible involvement of specific cell-mediated immunity and apoptotic pathways as well. Interestingly, CRP has been found to reflect circulating sex hormone levels and hormone replacement therapy ( 24 , 28–30 ), which we have previously linked to HF risk in the UK Biobank ( 31 ) and suggests the involvement of metabolic alterations in the pathway.…”
Section: Discussionmentioning
confidence: 75%
“…CRP is a pro-inflammatory cytokine that can trigger the release or is correlated with other inflammatory markers such as interleukin-6, interleukin-8 and tumor necrosis factor-α ( 27 ), which suggests possible involvement of specific cell-mediated immunity and apoptotic pathways as well. Interestingly, CRP has been found to reflect circulating sex hormone levels and hormone replacement therapy ( 24 , 28–30 ), which we have previously linked to HF risk in the UK Biobank ( 31 ) and suggests the involvement of metabolic alterations in the pathway.…”
Section: Discussionmentioning
confidence: 75%
“…The biological mechanisms underlying these relationships with heart diseases in humans remain unclear. However, studies have suggested links between mLOY and increased total and bioavailable testosterone 17 , metabolic biomarkers that we recently found to be associated with incident hospitalization for heart failure 18 .…”
Section: Introductionmentioning
confidence: 77%